Предмет: Алгебра, автор: lerusuk358

Помогите. Пожалуйста.

Приложения:

Ответы

Автор ответа: snow99
1
Вторая строчка снизу:
8 {a}^{2} x \times ( -  \frac{3}{4}  {x}^{3} ) =  - 6 {a}^{2}  {x}^{4}
( -  \frac{3}{4}  {x}^{3})  \times 2 {a}^{4} c = -  \frac{3}{2}  {a}^{4} c {x}^{3}
2 {a}^{4} c \times ( {a}^{3}  {c}^{2} x) ^{ 3 }  = 2 {a}^{13}  {c}^{7}  {x}^{3}
Третья строчка снизу:
6 {a}^{2}  {x}^{4}  \times ( -  \frac{3}{2}  {a}^{4} c {x}^{3} ) =  - 9 {a}^{6} c {x}^{7}
 -  \frac{3}{2}  {a}^{4} c {x}^{3}  \times 2 {a}^{13}  {c}^{7}  {x}^{3}  =  - 3 {a}^{17}  {c}^{8}  {x}^{6}
Верхняя:
 - 9 {a}^{6} c {x}^{7}  \times ( - 3 {a}^{17}  {c}^{8}  {x}^{6} ) = 27 {a}^{23}  {c}^{9}  {x}^{13}
Похожие вопросы